The social cure : identity, health and well-being - Jetten, Jolanda; Haslam, Catherine; Haslam, S. Alexander (Psychology Press, 2012)
(from the cover) A growing body of research shows that social networks and identities have a profound impact on mental and physical health. The challenge we face is explaining why this should be the case. What is it that social groups offer that appears to be just as beneficial as a daily dose of vitamin C or regular exercise? This edited book brings together the latest research on how group memberships, and the social identities associated with them, determine people's health and well-being. The volume provides a variety of perspectives that offer theoretical and empirical insights into these processes and their consequences. The contributions present an analysis of core theoretical issues relating to the ways in which social identities, and factors associated with them (such as social support and a sense of community), can bolster an individual's sense of self and contribute to physical and mental health. It is shown how social identities constitute a "social cure," capable of promoting adjustment, coping and well-being for individuals dealing with a range of illnesses, injuries, trauma, and stressors. In addition, these theories provide a platform for practical strategies that can maintain and enhance well-being, particularly among vulnerable populations. The book presents insights which have implications for health, clinical, social, and organisational psychology and a range of cognate fields. (PsycINFO Database Record (c) 2012 APA, all rights reserved)